The Pass-Through of Exchange Rate in the Context of the European Sovereign Debt Crisis - Nidhaleddine Ben Cheikh (FIW - Research Centre International Economics, 2013)
This paper investigates whether the exchange rate pass-through (ERPT) to CPI inflation is a nonlinear phenomenon for five heavily indebted euro area (EA) countries, namely the so-called GIIPS group (Greece, Ireland, Italy, Portugal, and Spain). Using logistic smooth transition models, we explore the existence of nonlinearity with respect to sovereign bond yield spreads (versus German) as an indicator of confidence crisis/macroeconomic instability. Our results provide strong evidence that the extent of ERPT is higher in periods of macroeconomic distress, i.e. when sovereign bond yield spreads exceed some threshold. For all the GIIPS countries, we reveal that the increasing of macroeconomic instability and the loss of confidence during the recent sovereign debt crisis has entailed a higher sensibility of CPI inflation to exchange rate movements.
Keywords: C22; E31; F31; 330; Exchange Rate Pass-Through; Inflation; Smooth Transition Regression